Regional specification of stomatal production by the putative ligand CHALLAH - Abrash, Emily B.; Bergmann, Dominique C. (Development (Cambridge), 2010)
The problem of modulating cell fate programs to create distinct patterns and distributions of specialized cell types in different tissues is common to complex multicellular organisms. Here, we describe the previously uncharacterized CHALLAH ( CHAL ) gene, which acts as a tissue-specific regulator of epidermal pattern in Arabidopsis thaliana. Arabidopsis plants produce stomata, the cellular valves required for gas exchange, in virtually all aerial organs, but stomatal density and distribution differ among organs and along organ axes. Such regional regulation is particularly evident in plants mutant for the putative receptor TOO MANY MOUTHS ( TMM ), which produce excess stomata in leaves but no stomata in stems. Mutations in CHAL suppress tmm phenotypes in a tissue-specific manner, restoring stomatal production in stems while minimally affecting leaves. CHAL is similar in sequence to the putative stomatal ligands EPF1 and EPF2 and, like the EPFs, can reduce or eliminate stomatal production when overexpressed. However, CHAL and the EPFs have different relationships to TMM and the ERECTA (ER) family receptors. We propose a model in which CHAL and the EPFs both act through ER family receptors to repress stomatal production, but are subject to opposite regulation by TMM. The existence of two such ligand classes provides an explanation for TMM dual functionality and tissue-specific phenotypes.